Surgical treatment and outcomes in aortic valve endocarditis and perivalvular abscesses - Ellelan Degife; Alyssa Morrison; Syed Bin Usman Mahmood; Sigurdur Ragnarsson; Andrea Amabile; Roland Assi; Prashanth Vallabjoyshula; Arnar Geirsson (Scientific Reports)
Abstract Patients with aortic root abscesses experience increased morbidity and mortality compared to those without abscess in aortic valve infective endocarditis. The superior intervention for patients with aortic root abscess is not determined. This research investigates the degree to which increased morbidity and mortality of aortic root abscess, and to describe perioperative characteristics and outcomes of root operations versus root-sparing repairs of aortic root abscess. All patients who underwent surgical treatment of active aortic valve endocarditis between 2011 and 2022 at a single institution were reviewed, yielding 218 patients, of whom 64 had perivalvular abscess. Patients were treated with either simple (root-sparing) or complex (root replacement) techniques. Patients with abscess demonstrated significantly higher rates of previous cardiac surgery, redo endocarditis surgery, aortocavitary fistula, heart block, and prosthetic valve endocarditis. One quarter of abscesses were not detected on preoperative imaging. Presence of abscess was a significant predictor of operative mortality. Prosthetic valve endocarditis was a significant predictor of complex repair in patients with abscess. Five-year survival was similar between simple and complex repair groups in patients with abscess. Aortic root abscess confers significant morbidity and mortality, and measures should be taken to ensure early detection and treatment of this condition.